Improved method of evaluating power losses in pulse converters of micro resistance welding machines - Bondarenko, O. F.; Ryzhakova, T. O.; Kozhushko, Yu. V. (Technology and design in electronic equipment, 2018)
The paper represents resistance welding characteristics and construction features of power supplies for resistance welding. The authors give an overview of circuit topologies of converters for resistance welding and distinguish the most promising one — the transistor buck converter with a synchronous transistor. It is shown that in order to ensure acceptable energy efficiency of power supply for resistance welding machines, while maintaining sufficient accuracy of current regulation in a welding contact, special modes of pulse transistor converters are used. The analysis of resistance welding features — high currents, low voltages — makes it possible to presume that the evaluation of the power losses in semiconductor elements only is insufficient and needs to be complemented by taking into account the losses on the inductive element of the converter circuit. In this work, the authors propose the method of estimating the power losses in the pulse buck converter of the power supply of resistance welding machine, which allows for more accurate calculations at the design stage due to consideration of the power losses on the inductive element of the circuit. The methodology is to calculate the total power losses as the sum of power losses on all individual elements of the circuit. Power losses on inductance is calculated using the Steinmetz equation. The calculations carried out with this technique proved the advisability of taking into account the power losses on the inductive element, especially in the region of high frequencies. The obtained diagrams demonstrated the dependency of the power losses in the converter on the frequency at different values of current and voltage.